Reimagining health services provision for neglected groups: The “personalization from below” phenomenon - Berti Suman, Anna; Heyen, Nils B.; Micheli, Marina (Frontiers in Sociology, 2023)
How can data-driven citizen science activities aimed at personalizing health services meet the needs of unrepresented and neglected communities? In this short Perspective, we explore ‘personalization from below’ as a phenomenon manifesting forms of citizen science-based data altruism that specifically push for and enact a different understanding of both public services and personalization. We develop the argument that such phenomenon taking place outside ‘institutionalized’ health systems could make health services provision more inclusive of values that matter to people. We contextualize the phenomenon, discuss emerging data governance models and alternative public health interventions, and conclude by outlining future research avenues.